(untitled) (World Science, 2016)
The using of negative impedance circuits expands the set of basic electrical circuit components by three additional components: a negative resistor, a negative capacitor and a negative inductor, respectively, R-, C-, L-negatrons. Definitions and the component equations of the circuit negatrons have been represented for time and frequency domains. The possibility of direct synthesis negative impedance circuits, which are based on operational amplifier with feedback circuits on both inputs, has been studied. Because of input signal’s amplitude and frequency band effects on the negative impedance circuit working stability, the investigations of the permissible excitation signals deviations for negative impedance circuits were carried out and results were obtained in numerical expressions. The numerical values of the boundaries of the operating range of currents and voltages are determined by the value of electromotive force source of the operational amplifier split power, parameters of feedback elements and signal frequency excitation. Simulation results using MultiSim software have proved the validity of the considered limitations on the operating range of input signals and their frequency for different types of negative impedance circuits.